Effectiveness of an Oral Health information, Education, and Communication Material on Knowledge, Attitudes, and Practices of Caregivers of Kindergarten Pupils in Aurora Quezon/Sittie Nor Rhizmin A. Tiang. - Tiang, Sittie Nor Rhizmin A., author; Mendoza, Michael Antonio F., technical adviser and co-author. (2019)
Objective. It has been recognized that the knowledge, attitudes, and practices (KAP) of
the caregivers affect the children’s oral and general health. Prevention of oral diseases,
like caries, can be achieved by giving an oral health education (OHE) to caregivers,
specifically mothers. Health educators have agreed that they are an important target
group for OHE being “key figures” that provide the greatest influence on their child’s life.
This study intended to use and test the effectiveness of an Oral Health Information,
Education, Communication (IEC) material which aimed to increase the caregivers’ oral
health KAP that would lead to dental visits of the children, regardless if symptomatic or
not.
Methods: A one-group pretest-posttest design was used in the kindergarten classes of a
public school in Manila, Philippines. The study utilized bilingual (Filipino-English)
information sheets, pre- and post-test questionnaires after a 21-day period, and an Oral
Health IEC material. Descriptive statistics were used to present and analyze the gathered
data from the caregivers of kindergarten pupils
Results: Though a low response rate of 9.93% was obtained (N=302) in the study, the
respondents have displayed adequate level of knowledge, positive attitude, and good
practice before the use of the IEC material. Significant improvement was noted with the
post-test after the 21-day follow-up period. A change in practice was observed wherein
13.33% of the respondents sent their child/ward to the dentist regardless if symptomatic
or not.
Conclusion: The Oral Health IEC material used was effective in increasing the KAP of
the caregivers. Factors like dental pain, advice from friends/family, and the caregiver’s
personal decision have contributed to the child’s dental visit after the 21-day period. The
results of this study cannot be generalized to the entire population due to the low response
rate.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Pedodontics